The Use of English Slang Words in Informal Communication Among 8th Semester Students of English Department in Binus University - Muhartoyo Muhartoyo; Baby Samantha Wijaya (Bina Nusantara University, 2014)
English slang is often used in informal communication. The purposes of this study are to find out the reason of using English slang, how students acquire English slang, and what kind of slang that they mostly use. This study uses qualitative method with the paradigm of experimental design to obtain quantitative data which are then analyzed using interpretative analysis. To collect the data, writers distributed questionnaire to 30 respondents randomly. The findings show that more than half of the respondents say that the reason behind the usage of English slang words is to cut down the time when talking, texting, or tweeting. TV and film are the most frequently used source for acquiring English slang words. The type of slang word which is most frequently used by the respondents is acronym. The result of the analysis also shows that although all respondents say that they know and think English slang words are interesting, more than a half of respondents say that they seldom use English slang words in communication. They still use standard words in informal communication. It is also found that English slang words that they acquire are not many. When they were ordered to write other English slang words they know and use, many respondents answered just one or two words; and even three respondents wrote nothing.